2023
DOI: 10.3389/frwa.2023.1047955
|View full text |Cite
|
Sign up to set email alerts
|

Working together: A study of civil society partnerships between WASH (water, sanitation, and hygiene) and GESI (gender equality and social inclusion) organisations in Timor-Leste

Abstract: This article reports on an empirical study conducted in Timor-Leste that explored the drivers, benefits, and challenges of partnerships and collaborations between water, sanitation, and hygiene (WASH) and gender equality and social inclusion (GESI) organisations as integral parts of the WASH system. The research design was primarily qualitative and included a data-collection workshop with 30 representatives from 16 civil society organisations (CSOs) in Dili, longitudinal research involving two rounds of semi-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The literature on partnerships between WASH organisations and other types of organisations in the Blue Pacific region is scant, with most studies related to WASH and gender equality and inclusion partnerships in Timor-Leste [6,7] (which is included in this study as being part of the Blue Pacific region, see Appendix A). The study from Timor-Leste found that fourteen distinct benefits of WASH and gender equality and social inclusion partnerships were identified by research participants, relating to three main areas: (1) increasing participation and inclusion of women in WASH programs and related decisions; (2) mutual learning and capacity building, advocacy opportunities and connections with government; and (3) shifts in gender norms (changing perceptions of roles and responsibilities related to WASH).…”
Section: Wash Sector Partnerships In the Blue Pacificmentioning
confidence: 99%
See 4 more Smart Citations
“…The literature on partnerships between WASH organisations and other types of organisations in the Blue Pacific region is scant, with most studies related to WASH and gender equality and inclusion partnerships in Timor-Leste [6,7] (which is included in this study as being part of the Blue Pacific region, see Appendix A). The study from Timor-Leste found that fourteen distinct benefits of WASH and gender equality and social inclusion partnerships were identified by research participants, relating to three main areas: (1) increasing participation and inclusion of women in WASH programs and related decisions; (2) mutual learning and capacity building, advocacy opportunities and connections with government; and (3) shifts in gender norms (changing perceptions of roles and responsibilities related to WASH).…”
Section: Wash Sector Partnerships In the Blue Pacificmentioning
confidence: 99%
“…(1) organisational and operational barriers that prevented realisation of outcomes, especially when staff changed (2) weak links in the WASH system due to siloing and (3) power dynamics and challenges to organisational and interpersonal relationships [7].…”
Section: Wash Sector Partnerships In the Blue Pacificmentioning
confidence: 99%
See 3 more Smart Citations